Effect of Lycopene on the Growth Performance, Antioxidant Enzyme Activity, and Expression of Gene in the Keap1-Nrf2 Signaling Pathway of Arbor Acres Broilers - Wang, Sibo; Wu, Hongzhi; Zhu, Yunhui; Cui, Hongxia; Yang, Ji; Lu, Mingyuan; Cheng, Huangzuo; Gu, Lihong; Xu, Tieshan; Xu, Li (Frontiers in Veterinary Science, 2022)
The objective of this study was to determine the effect of dietary lycopene supplementation on the growth performance, antioxidant enzyme activity of serum and liver, and gene expressions associated with Kelch-like ech-associated protein-1 (Keap1) / Nuclear Factor E2-related factor 2 (Nrf2) pathway in liver of Arbor Acres broilers. 288 1-day-old male broilers were randomly divided into 4 treatments with 6 replicates and 12 for each replicate. The control group was fed with the basal diet, while the treated groups were fed with the basal diet with 10, 20, 30 mg/kg lycopene in powder. Feed and water were provided ad libitum for 42 days. Compared with the control group, a) the average daily gain increased (P = 0.002 vs. P = 0.001) and the feed conversion ratio decreased (P = 0.017 vs. P = 0.023) in groups treated with lycopene in the grower and whole phases, and the average daily feed intake was quadratically affected (P = 0.043) by lycopene in the grower phase; b) the serum superoxide dismutase content was linearly affected (P = 0.035) by lycopene at 21d; c) the serum glutathione peroxidase content, superoxide dismutase content and total antioxidant capability were higher (P = 0.014, P = 0.003, P = 0.016, respectively) in 30 mg/kg lycopene group at 42 d; d) the liver glutathione peroxidase and superoxide dismutase contents in groups treated with lycopene were higher (P = <0.001 vs. P = <0.001) at 21 d; e) the liver glutathione peroxidase content was higher (P = <0.001) in 20 and 30 mg/kg lycopene groups, at 42 d; f) the mRNA expression levels of Nrf2, superoxide dismutase 2, NAD(P)H quinone dehydrogenase 1 and heme oxygenase 1genes were higher (21 d: P = 0.042, P = 0.021, P = 0.035, P = 0.043, respectively; 42 d: P = 0.038, P = 0.025, P = 0.034, P = 0.043, respectively) in 20 and 30 mg/kg lycopene groups at 21 and 42 d. The 30 mg/kg lycopene concentration improved the growth performance, antioxidant enzyme activity in serum and liver, and gene expression in Keap1-Nrf2 signalling pathway of Arbor Acres broilers.